Conceptualizing the Effect of Community and Neighborhood Factors on Type 2 Diabetes Health Outcomes. (June 2017) - Smalls, Brittany L.; Gregory, Chris M.; Zoller, James S.; Egede, Leonard E.
The objective of this study was to validate a conceptual framework of the relationship between neighborhood factors and diabetes process and outcomes in type 2 diabetes. Structural equation modeling was used to conduct path analysis to examine relationships between neighborhood characteristics and diabetes self-care and glycemic control based on an adapted conceptual framework. Medication adherence and social cohesion has significant direct effects on glycemic control. There was an indirect effect between social support and glycemic control, where 46% of the effect was mediated by medication adherence. Last, medication adherence, food insecurity, and social cohesion had significant total effects on glycemic control. Furthermore, walking environment, social support, neighborhood safety, and neighborhood problems had significant direct effects on food insecurity. The modified conceptual model was validated using path analysis, and neighborhood characteristics had direct and indirect effects on glycemic control.